A Mathematical Model for Estimating the End-of-Life of Power Transformers: From Literature Review to Development Analysis - Ganiyu Adedayo Ajenikoko; Ogunmakinde Jimoh Ogunwuyi (Universitas Pendidikan Indonesia (UPI), 2022)
A power transformer used to transfer electrical energy in any part of the electrical or electronic circuit between the generator and distribution primary circuits. The aims of this study was to developed a mathematical model for determining the End-of-life of power transformers. The paper employed the use of 2-Furaldehyde (2FAL) content values of 0.5 ppm to 10ppm and Arrhenius Parameters in determining the Degree of Polymerization (DP) of the transformer using Jacobi and Gauss-Seidel numerical analysis iterative techniques. The techniques were implemented in a MATLAB environment. The End-of-life of the transformer was determined by adding the service age at any point in time to the remaining lifetime at that point. The developed mathematical model yielded a DP range of 247 ≤ DP ≤ 1184 with a lifespan of 273678 hours for a virgin transformer, based on a constant hotspot temperature of 1100C. The developed model gave a better approach to determining the end-of-life of power transformers based on the parameters of insulation level and the temperature of the system. Therefore, by effective control of the condition of operation, it would be possible to estimate the useful lifetime of a power transformer at any time.